Biomedical Perspective of Electrochemical Nanobiosensor - Singh, Priti; Pandey, Shailendra Kumar; Singh, Jyoti; Srivastava, Sameer; Sachan, Sadhana; Singh, Sunil Kumar (Nano-Micro Letters, 2015)
Electrochemical biosensor holds great promise in the biomedical area due to its enhanced specificity, sensitivity, label-free nature and cost effectiveness for rapid point-of-care detection of diseases at bedside. In this review, we are focusing on the working principle of electrochemical biosensor and how it can be employed in detecting biomarkers of fatal diseases like cancer, AIDS, hepatitis and cardiovascular diseases. Recent advances in the development of implantable biosensors and exploration of nanomaterials in fabrication of electrodes with increasing the sensitivity of biosensor for quick and easy detection of biomolecules have been elucidated in detail. Electrochemical-based detection of heavy metal ions which cause harmful effect on human health has been discussed. Key challenges associated with the electrochemical sensor and its future perspectives are also addressed.